2006
DOI: 10.1136/oem.2006.027987
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced preventive programme at a beryllium oxide ceramics facility reduces beryllium sensitisation among new workers

Abstract: A comprehensive preventive programme reduced beryllium sensitisation in new workers during the first years of employment, despite airborne beryllium levels for production workers that were similar to pre-programme levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…The high correlation among the three metals suggests that improved housekeeping for certain categories of surfaces would go a long way toward reducing overall contamination and potential for metalinduced sensitization in each facility. Cummings et al (2007) reported that an enhanced industrial hygiene preventive program, incorporating novel interventions to minimize particle migration and both respiratory and dermal exposures, reduced beryllium sensitization among newly hired workers in the first years of employment. Another example related to cleanliness criteria is the nickel release limit established by the European Union to prevent nickel sensitization and contact dermatitis in the general public (where release rate is determined by immersion of nickel-containing consumer products in artificial sweat) (Lide´n et al, 1996).…”
Section: Exposure Controlmentioning
confidence: 99%
“…The high correlation among the three metals suggests that improved housekeeping for certain categories of surfaces would go a long way toward reducing overall contamination and potential for metalinduced sensitization in each facility. Cummings et al (2007) reported that an enhanced industrial hygiene preventive program, incorporating novel interventions to minimize particle migration and both respiratory and dermal exposures, reduced beryllium sensitization among newly hired workers in the first years of employment. Another example related to cleanliness criteria is the nickel release limit established by the European Union to prevent nickel sensitization and contact dermatitis in the general public (where release rate is determined by immersion of nickel-containing consumer products in artificial sweat) (Lide´n et al, 1996).…”
Section: Exposure Controlmentioning
confidence: 99%
“…Animal studies of lung disease development with exposures to beryllium and isocyanates have shown that skin exposure can lead to an immunologic response (sensitization) that can later result in respiratory disease [Bello et al 2007;Redlich et al 2008]. Recent evaluation of a chronic beryllium lung disease prevention program showed a decrease in the rate of worker sensitization to beryllium after skin protection was added [Cummings et al 2007]. Most cobalt-related asthma likely involves immunologic sensitization to cobalt that might be prevented by skin protection.…”
Section: Exposure-response Modelsmentioning
confidence: 99%
“…Animal studies of lung disease development after exposures to beryllium and isocyanates have shown that skin exposure can lead to an allergic response (sensitization) that can later manifest as allergic respiratory disease [Bello et al 2007;Redlich et al 2008]. Recent evaluation of a chronic beryllium lung disease prevention program which included skin protection showed a decrease in the rate of worker sensitization to beryllium [Cummings et al 2007]. …”
Section: Health Hazard Evaluation Report 2007-0327-3083mentioning
confidence: 99%